STRUKTUR KEPEMILIKAN SAHAM DAN KONDISI KEUANGAN PERUSAHAAN PENGARUHNYA TERHADAP KEBIJAKAN HUTANG (Studi Pada Perusahaan Manufaktur di Pasar Modal Indonesia) - HADI SUSANTO (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
This study was based on agency theory and the theory of capital structure. The development of agency theory that describes the ownership structure can affect firm performance by adjusting the way the agency conflict between management and shareholders in capital structure theory describes that the debt could obtain tax savings, but on the other hand it may cause financial distress costs. This study aims to determine the effect of stock ownership structure and financial condition of debt policy. Shareholding structure consists of managerial ownership and institutional ownership. The financial condition of the company consists of the company's growth, the value of the pledged assets, and liabilities other than tax savings. The population of this research are manufacturing companies go public to be listed on the Indonesia Stock Exchange (BEI). The sample was based on purposive sampling method based on certain criteria, there are 73 companies that qualify as research samples. Data were collected from 73 companies, from 2005 until 2007, so we get the unit of analysis pooling data with 219 observations. Based on the results of regression analysis, the first managerial ownership has a negative but not significant effect on debt policy. Both institutional ownership has a negative and significant impact on debt policy. All three firms have positive growth and no significant effect on debt policy. The fourth company was pledged assets has positive and significant impact on debt policy. Fifth tax savings than debt significantly and negatively related to debt policy.